Epidemiology of urogenital injuries in the Regional Specialist Hospital in Puławy in years 2007 -2018 - Kamiński, Piotr; Jankowska, Paula; Jankowski, Krzysztof; Nogalski, Adam; Ciechan, Janusz (Journal of Education, Health and Sport, 2019)
IntroductionTrauma is defined as damage to cells, tissues and organs caused by external factors acting on them. According to WHO data, trauma caused 4.8 millions of deaths in 2016. Urogenital trauma occurs in 10% of all the injuries in the human population.Aim of the studyThe aim of this study was to characterize the patients treated for injuries in Urology Department in Regional Hospital in Poland and compare the results with the data from literature.Material and methodsThe study involved patients hospitalized in Regional Specialist Hospital in Puławy, Poland from 2007 to 2018. The survey was based at analysis of medical documentation. The collected data has been subjected to statistical analysis. 66 patients were included in the study group. Their average age was 43.25 years.ResultsThe absolute majority of patients were men – 81.81% (n=54), women – 18.18% (n=12). The average age for males was 42.27 and for the females – 44.25. Most frequent trauma in our study was the renal trauma 36.36% (n=24). 47.06% of this injuries were associated with MVA's. The second most frequent group was a genital trauma - 21 patients (31,81%). 81.81 % of them required surgical treatment. Another group constituted 10.6 % (n=7) were the patients treated for bladder injury. Penis was injured in 6.06% (n=4), 75% of patients required a surgery. Urether has been injured only in 4.55%.ConclusionsKidney is the most frequent organ of genitourinary tract, affected by trauma, particularly during MVA's. Victims are usually treated conservatively. External genitalia injuries, especially male, are also very frequent. Mostly patients need a rapid surgical intervention but appropriate treatment allows the patient to recover completely without any lasting disability